1966
DOI: 10.1139/f66-105
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oxygen in Relation to Temperature on the Development of Embryos of Brook Trout and Rainbow Trout

Abstract: Embryos of the brook trout (Salzteli,nus Jontinalis Mitchill) were incubated in reduced levels of dissolved oxygen of approximately 2.5 ppm, 3.5 ppm, 4.5 ppm, and a control level near air-saturation (10 ppm) at each four temperatures, 2.5, 5.0, 7.5, and 10.0 C, from fertilization to a late stage of development. Embryos of the rainbow trout (Salmo guird.nerd Richardson) were incubated in a similar experiment at levels of oxygen approximating 2.5 and 3.5 ppm and a level near air-saturation at each of the four te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0
1

Year Published

1979
1979
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(41 citation statements)
references
References 0 publications
3
37
0
1
Order By: Relevance
“…Undoubtedly, the fluctuating temperature regimes used by Smith and Fahay (1970) and Smigielski (1975) prolonged the development period, although other abiotic factors could account for some of the differences. For example, dissolved oxygen content, which was not determined in any of the studies, has been shown to alter development times by as much as 31 V0 (Garside, 1966).…”
Section: Discussionmentioning
confidence: 92%
“…Undoubtedly, the fluctuating temperature regimes used by Smith and Fahay (1970) and Smigielski (1975) prolonged the development period, although other abiotic factors could account for some of the differences. For example, dissolved oxygen content, which was not determined in any of the studies, has been shown to alter development times by as much as 31 V0 (Garside, 1966).…”
Section: Discussionmentioning
confidence: 92%
“…1) (Garside, 1966;Miller et al, 2008), as well as distinct alterations of the blood-O 2 transport system. The first possibility is that the decrease in overall Hb concentration and retention of embryonic erythrocytes in stage-matched hypoxia-reared larvae may be associated with a general metabolic depression.…”
Section: Early Ontogenetic Strategies For Coping With Hypoxiamentioning
confidence: 99%
“…Hypoxia delays development in fishes (e.g. Alderdice et al, 1958;Garside, 1959Garside, , 1966Silver et al, 1963;Miller et al, 2011;Bianchini and Wright, 2013;Robertson et al, 2014). In contrast, embryos of amphibious fishes may experience relatively high oxygen availability if deposited out of water because the diffusion coefficient of oxygen in air is ∼8000 times higher than in water, and boundary layers in air are also much smaller (Dejours, 1988).…”
Section: Introductionmentioning
confidence: 99%